2018
DOI: 10.1111/1467-923x.12457
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of Political Ambition in Britain

Abstract: Representative democracies require sufficient numbers of citizens to put themselves forward as candidates for political office. Existing studies have shown that political institutions are not representative of the population as a whole, suggesting that political ambition is not evenly distributed across all potential candidates. We discuss evidence from the first systematic study of political ambition in Britain, examining the question of who is interested in putting themselves forward for political office. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 6 publications
1
10
1
Order By: Relevance
“…Studies in the US have shown that women often consider themselves less likely to enter political life, show less ambition to run for political office and are less certain that they could run a successful campaign (Fox and Lawless, 2011; Kanthak and Woon, 2014). Allen and Cutts (2018) show that people indicating ambition to run for public office in the UK are quite different from the general population: Individuals with higher education levels, from privileged backgrounds and men are more likely to show political ambition. While ambition as a measure of self-selection seems to stop women from running for office, this problem appears to also apply more generally to people from outside the political class that has controlled Britain’s politics (Allen and Cairney, 2017).…”
Section: Parties Nominating Womenmentioning
confidence: 95%
“…Studies in the US have shown that women often consider themselves less likely to enter political life, show less ambition to run for political office and are less certain that they could run a successful campaign (Fox and Lawless, 2011; Kanthak and Woon, 2014). Allen and Cutts (2018) show that people indicating ambition to run for public office in the UK are quite different from the general population: Individuals with higher education levels, from privileged backgrounds and men are more likely to show political ambition. While ambition as a measure of self-selection seems to stop women from running for office, this problem appears to also apply more generally to people from outside the political class that has controlled Britain’s politics (Allen and Cairney, 2017).…”
Section: Parties Nominating Womenmentioning
confidence: 95%
“…There is ample evidence that voters draw on a variety of heuristics, including gender, to simplify vote choice (Cutler 2002;Ditonto 2017;Fiske and Taylor 2013;McDermott 2005McDermott , 2009. The literature shows a clear association between power and masculinity, with men stereotyped as the most capable, competent, qualified, and likeable political candidates (Allen and Cutts 2018;Bauer 2020b;Butler and Preece 2016;Conroy 2015;Crowder-Meyer 2013;Ditonto 2017;Goodyear-Grant 2013;Holman and Schneider 2018;Pruysers and Blais 2018;Sanbonmatsu 2002). Nonetheless, much of the research on stereotypes focuses on the national and state levels (Alexander and Andersen 1993;Bauer 2020a;Bauer and Santia 2021;Conroy 2015;Dunaway et al 2013;Fowler and Lawless 2009;Jamieson 1995;Windett 2014).…”
Section: Gendered Stereotypes As An Explanation For Women's Political...mentioning
confidence: 99%
“…When exploring ambition in particular, a healthy research agenda examines how gender influences nascent ambition and why women are less likely to be politically ambitious than men (Fox and Lawless 2011;Lawless and Fox 2015;Preece, et al, 2016;Schneider, et al, 2016;Crowder-Meyer 2018;Pruysers and Blais 2018). Other scholars investigate how variation in personality traits like the Big 5 and social background beyond gender affects nascent ambition (Allen and Cutts 2017;Blais and Pruysers 2017;Allen and Cutts 2018;Dynes, et al, 2019).…”
Section: Dark Traits Personality and Political Correlatesmentioning
confidence: 99%